Clinical reproducibility of different centric relation recording techniques in edentulous individuals: An observational cross-sectional study - de Sousa Ervolino, Isabela Caroline [UNESP]; Goiato, Marcelo Coelho [UNESP]; de Moraes Melo Neto, Clóvis Lamartine [UNESP]; de Caxias, Fernanda Pereira [UNESP]; da Silva, Emily Vivianne Freitas; Túrcio, Karina Helga Leal [UNESP]; dos Santos, Daniela Micheline [UNESP] (Wiley, 2022)
Purpose: To assess the reproducibility of four different centric relation (CR) recording techniques, and time spent performing each technique in edentulous individuals. Materials and methods: Four techniques were assessed: extraoral gothic arch (EOGA) tracing, intraoral gothic arch (IOGA) tracing, deglutition (D), and frontal manipulation with tongue elevation (FMTE). Twelve subjects participated in the study; four technique records were performed on each volunteer by the same operator. Each record was repeated three times, in the same period of the day, with a 30 min interval between each technique. The reproducibility of each technique was assessed by the tri-dimensional displacement of the position of the condylar housing (mandible condyle) to the wall of the condylar guide (glenoid cavity) in the semi-adjustable articulator (anteroposterior, mediolateral, and superior–inferior). The time spent on each technique was timed in seconds (from the beginning of each technique until the wax occlusion fixation). The analysis of variance (ANOVA) and the Tukey test were performed for anteroposterior displacement (two-way) and for time spent on CT recording techniques (one-way) (α < 0.05). Regarding mediolateral and superior–inferior displacements, the nonparametric Kruskal–Wallis was performed for the comparison between recording methods, whereas the Mann–Whitney test was performed for the comparison between sides (α < 0.05). Results: The factor recording technique interfered with the anteroposterior displacement (ANOVA: α < 0.001; F = 11.396). The technique D (right side: 3.78 ± 0.69 mm; left side: 3.45 ± 0.74 mm) showed a statistically significant difference compared to the other techniques (EOGA: right side: 3.00 ± 0.00 mm; left side: 3.00 ± 0.00 mm; FMTE: right side: 2.81 ± 0.52 mm; left side: 2.82 ± 0.79 mm; IOGA: right side: 2.90 ± 0.65 mm; left side: 3.12 ± 0.44 mm). The time spent on the recording technique influenced the results (ANOVA: α < 0.001; F = 21.118). The IOGA (340.40 ± 163.41 s) and EOGA (285.93 ± 133.84 s) required more time compared to the D (86.00 ± 34.33 s) and FMTE (101.33 ± 36.72 s) techniques. Conclusion: Graphic recordings showed better reproducibility and accuracy of the position of the centric relation.
Keywords: centric relation; complete denture; recording techniques; reproducibility